Successful blind lung isolation with the use of a novel double-lumen endobronchial tube in a patient undergoing lung transplantation with massive pulmonary secretion: A case report. Issue 33 (August 2019) - Seo, Yijun; Kim, Namo; Paik, Hyo Chae; Park, Dahee; Oh, Young Jun
Abstract: Rationale: Precise lung isolation technique with visual confirmation is essential for thoracic surgeries to create a safe and clear surgical field. However, in certain situations, such as when patients have massive pulmonary secretion or when the fiberoptic bronchoscopy (FOB) is not applicable, lung isolation has been performed blindly. Patient concern: A 52-year-old woman, whose airway was unable to visualize with FOB due to massive pulmonary secretion, was presented for bilateral sequential lung transplantation. Extracorporeal membranous oxygenation, tracheostomy, and mechanical ventilation were applied to the patient for 39 days preoperatively as a bridge for lung transplantation. Diagnosis: Patient was diagnosed with an idiopathic pulmonary fibrosis and obesity. Intervention: Initially, height-based blind positioning with a conventional double-lumen endobronchial tube (DLT) failed to ventilate the patient properly, and the confirmation of DLT positioning with FOB was impossible due to massive pulmonary secretion. Therefore, a novel DLT (ANKOR DLT) that has one more cuff, located at a point between the distal opening of the tracheal lumen and the starting point of bronchial cuff, than conventional DLT was used for the lung isolation in the patient. Outcomes: After the completion of lung graft, FOB finding showed that the ANKOR DLT was optimally positioned at the tracheobronchial tree of the patient, and its depth was 2.5 cm shallower than that of the conventional tube. Lessons: ANKOR DLT would be a feasible choice to achieve successful blind lung isolation when the use of FOB is impossible to achieve the optimal lung isolation.